Perubahan Fungsi Bangunan dan Pengaruhnya Terhadap Karakteristik Enclosure Ruang Jalan Studi Kasus Jl. Jend. Nasution, Kota Metro - Yunita Kesuma (Universitas Muslim Indonesia, 2020)
Jalan A.H. Nasution is one of the main movements of Metro city that connects the center of Metro City with the Eastern region (Kab. Lampung Timur) and has a strong historical character, characterized by rows of old Mahogany 80cm in diameter and 25 meters south of the street. Along with its development, this street is direct a primary collector and tourism industry service area in the form of hotels, restaurants, souvenirs, and other entertainment (RTRW Kota Metro 2011–2031) growth of the formal and informal commercial sector that occupies pedestrian lines and street bodies in several Jalan A.H. Nasution becomes a potential as well as a problem for Metro city. This study aims to obtain an overview of how changes in the typology of building functions affect the characteristics of the Jalan A.H. Nasution. The method used is qualitative rationalism, starting with the observation of collecting aerial photos and maps of the area, shooting the condition of the street, depicting two-dimensional street sections, and in-depth interviews with several sources, as well as analysis based on the theoretical basis of the visual character of the street space. The results of the study conclude that the change in the function of the building has implications for the fading of the characteristic of the street space enclosure due to changes in the setting of the physical elements forming the character of the Jalan A.H. Nasution's history, especially the change in residential functions to mixed, the decreasing intensity of old mahogany vegetation, the privatization of pedestrian green lanes, and the irregularity of building setbacks